The effects of dietary fish oil on exercising skeletal muscle vascular and metabolic control in chronic heart failure rats - Holdsworth, Clark T.; Copp, Steven W.; Hirai, Daniel M.; Ferguson, Scott K.; Sims, Gabrielle E.; Hageman, Karen S.; Stebbins, Charles L.; Poole, David C.; Musch, Timothy I. (My University, 2014)
The ATP-sensitive K+ (KATP) channel is a class of inward rectifier K+ channels that can link cellular metabolic status to vasomotor tone across the metabolic transients seen with exercise. This investigation tested the hypothesis that if KATP channels are crucial to exercise hyperaemia then blockade via glibenclamide (GLI) would lower hindlimb skeletal muscle blood flow (BF) and vascular conductance (VC) during treadmill exercise. In 14 adult male Sprague Dawley rats mean arterial pressure (MAP), blood [lactate], and hindlimb muscle BF (radiolabelled microspheres) were determined at rest (n = 6) or during exercise (n = 8; 20 m min⁻¹, 5% incline) under control (CON) and GLI conditions (5 mg kg⁻¹, i.a). At rest and during exercise, MAP was higher (Rest, CON: 130 ± 6, GLI: 152 ± 8; Exercise, CON: 140 ± 4, GLI: 147 ± 4 mmHg, P < 0.05) and heart rate (HR) was lower (Rest, CON: 440 ± 16, GLI: 410 ± 18; Exercise, CON: 560 ± 4, GLI: 540 ± 10 beats min⁻¹, P < 0.05) with GLI. Hindlimb muscle BF (CON: 144 ± 10, GLI: 120 ± 9 ml min⁻¹ (100 g)⁻¹, P < 0.05) and VC were lower with GLI during exercise but not at rest. Specifically, GLI decreased BF in 12, and VC in 16, of the 28 individual hindlimb muscles and muscle parts sampled during exercise with a greater fractional reduction present in muscles comprised predominantly of type I and type IIa fibres (P < 0.05). Additionally, blood [lactate] (CON: 2.0 ± 0.3; GLI: 4.1 ± 0.9 mmol L⁻¹, P < 0.05) was higher during exercise with GLI. That KATP channel blockade reduces hindlimb muscle BF during exercise in rats supports the obligatory contribution of KATP channels in large muscle mass exercise-induced hyperaemia.
Keywords: Blood flow; Conductance; Glibenclamide